Strengthening Islamic Education in the Era of Global Disruption: Integrating Science, Religion, and Pedagogical Innovation at Al-Ittifaqiah Indralaya Islamic Boarding School - Ulfa Hoyriah; Muhammad Wahyudi; Novi Ulfa Safitri; Agus Rifki Ridwan; Dinda Putri Januarta Putri Januarta (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2026)
This research is motivated by the challenges of globalisation, technological developments, and the dichotomy between religious studies and science that still influences Islamic education practices. This study is important to show how Islamic boarding schools respond to these challenges while maintaining their Islamic identity. This study aims to analyse strategies for strengthening Islamic education in an era of global disruption through the integration of science, religion, and pedagogical innovation at the Al-Ittifaqiah Indralaya Islamic boarding school. This study uses a qualitative approach with a case study design. Data was collected through in-depth interviews with pesantren leaders, teachers, and students, participatory observation of the learning process, and analysis of curriculum documents and institutional policies. Data analysis techniques were carried out thematically with stages of data reduction, data presentation, and conclusion drawing, accompanied by triangulation of sources and techniques to maintain the validity of the findings. The results of the study indicate that the integration of science and religion at Al-Ittifaqiah Islamic Boarding School has been implemented contextually through value-based learning, strengthening scientific ethics, and adaptive pedagogical innovations. This integration contributes to strengthening the character of students, increasing the relevance of learning, and preparing them to face global challenges, despite limitations in the formal curriculum and digital literacy of educators. This study is limited to one pesantren location, so the generalisation of the findings is limited. However, the results of this study have important implications for the development of an adaptive integrative Islamic education model for the era of global disruption. This study offers a conceptual and empirical framework for the integration of science, religion, and pesantren-based pedagogical innovation that can be used as a reference for the development of Islamic education and further research. Keywords: Islamic education, integration of science and religion, pedagogical innovation, Islamic boarding schools, global disruption